Frequency of Cesarean Deliveries in Women with Gestational Thrombocytopenia - Riasat, Zartasha; Bushra; Shafaq; Mahrukh (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the frequency of cesarean deliveries in women with gestational thrombocytopenia. Study type: cross sectional study. Settings: Department of Obs & Gynae, Khan Research Laboratories (KRL) Hospital Islamabad. Duration of study: 25th February 2025 to 24th May 2025. Methodology: Eighty women with singleton pregnancies, no structural abnormalities on obstetrical ultrasound, and gestational thrombocytopenia between the ages of twenty and forty were included.  The following conditions were excluded: history of anti-phospholipid anti-body syndrome, immune thrombocytopenia purpura or systemic lupus erythematosus, history of chronic hypertension, diabetes mellitus, liver or renal disease, human immunodeficiency virus infection, hepatitis C infection, or hepatitis B infection; pregnancies complicated by gestational hypertensive disorders, including pre-eclampsia and eclampsia; pregnancies complicated by HELLP (Hemolysis elevated liver enzymes low platelet) syndrome. Every patient underwent obstetrical ultrasonography, which was carried out by a single, skilled CPSP fellow radiologist. One skilled gynecologist, a fellow of the CPSP, performed cesarean deliveries. Results: The study's participants ranged in age from 20 to 40 years, with a mean age of 28.54 ± 5.93 years. Mean gestational age was 33.43 ± 3.52 weeks. Mean platelet count was 123509.43 ± 45638.43/µL. 31 (38.75%) women with gestational thrombocytopenia had undergone cesarean delivery. Conclusion: This study concluded by highlighting the serious fetal problems linked to gestational thrombocytopenia. A tendency toward higher maternal morbidity is indicated by the rising rate of cesarean deliveries.